Fitness and athletic development programs for people with disabilities - Benzidane, Hocine; ben bernou, athmane (sports creativity, 2025)
People with disabilities are individuals with physical, motor, sensory, or intellectual impairments. They can be categorized into those with visible disabilities, such as the blind, deaf, intellectually disabled, or those with physical disabilities like paralysis and amputation, and those with hidden disabilities, such as those with chronic illnesses like heart disease, diabetes, and asthma. People with disabilities require both general and specific physical fitness, and this fitness level varies depending on the degree and severity of the disability. Physical fitness is the general ability to adapt and respond positively to physical exertion. The level of physical fitness depends on an individual's health status and body composition, including their performance in various physical activities. Improvement and growth in the components of physical fitness occur as a result of the body's response to specific training exercises. The specific nature of each component of physical fitness leads to overall fitness for the individual, as improvement does not occur in one particular part or organ to the exclusion of others. Rather, the focus of training on each component determines its effectiveness. It is known that the body responds to structured and regulated physical exercise, enabling it to perform its functions at a high level. For example, repetition helps the body perform exercises easily and leads to improved functions. The more intense the training, the greater the body's response and ability to perform optimally according to its condition. Physical fitness components can improve rapidly through structured training, but they can also be lost quickly if the established exercise routine is discontinued. While it is necessary to determine the specific physical and motor fitness requirements of people with disabilities, we seek alternatives in programs tailored to this group. With the diversity of modern training methods and techniques, the sports coach must, before determining the optimal methods to improve athletic or physical performance, assess the individual's current performance level by measuring their physical and motor abilities and potential. This allows them to design a suitable program and, consequently, choose the most appropriate methods for developing and improving physical fitness, whether for health or high-level athletic achievement.